Lisa H. Sideris, Consecrating Science: Wonder, Knowledge, and the Natural World - Callicott, J. Baird (Journal for the Study of Religion, Nature and Culture, 2018)
Lisa H. Sideris, Consecrating Science: Wonder, Knowledge, and the Natural World (Oakland: University of California Press, 2017), xi + 300 pp., $34.95 (pbk), ISBN: 9780520294998.